2004
DOI: 10.1089/pho.2004.22.483
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Controlled 830-nm Low-Level Laser Therapy of Experimental Pressure Ulcers

Abstract: These results demonstrate that the salutary effects of LLLT on wound healing are temperature independent in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 10 publications
0
21
0
Order By: Relevance
“…Near-infrared low-level laser therapy (LLLT) under temperature-controlled conditions have been tested for their influences on ulcer healing [140]. No evidence was found that justifies using low-level laser therapy as an adjuvant to the consensus decubitus ulcer treatment [140].…”
Section: Laser Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Near-infrared low-level laser therapy (LLLT) under temperature-controlled conditions have been tested for their influences on ulcer healing [140]. No evidence was found that justifies using low-level laser therapy as an adjuvant to the consensus decubitus ulcer treatment [140].…”
Section: Laser Treatmentmentioning
confidence: 99%
“…No evidence was found that justifies using low-level laser therapy as an adjuvant to the consensus decubitus ulcer treatment [140].…”
Section: Laser Treatmentmentioning
confidence: 99%
“…• C and complete wound closure at 25 ± 6 days [12]. The results also showed that the group receiving incandescent light had a 36.3 ± 4.8% wound closure at day 14 while the group receiving laser therapy showed a significantly higher rate of wound closure at 75.4 ± 7.2% [12].…”
Section: Laser Chemistrymentioning
confidence: 78%
“…Little information is available regarding the potential thermal effects of near-infrared photoradiation during lowlevel laser therapy (LLLT) [12]. Lanzafame et al [12] studied the effect of temperature-controlled 830 nm LLLT on experimental pressure ulcers created in C57BL mice and reported that the group receiving laser therapy (830 nm 5 J/cm 2 , CW) showed a maximum temperature change during therapy of 2.0 ± 0.64…”
Section: Laser Chemistrymentioning
confidence: 99%
See 1 more Smart Citation